The Diagram of Thermostating Control System of Well Devices - Belyanin L. N. (2005, 2005)
The authors of the paper showed that effective ways of solving the problem of thermostating regulation of well technique units are using actual system comprising both the heater and the cooler. In this case for providing proportional law of control at close range of temperature stating system and decreasing heat release in electronic diagram it is proposed to apply pulse-duration modulation (PDM). In the given paper the problems of constructing electronic diagram of control by means of the heater and thermoelectric cooling module of the system of thermostating will be considered.